The Fornicator Sins against his own Body (1 Cor 6:18c) - Murphy-O'Connor, J. 1935-2013 (2008)
Closer attention to the meaning of ‘Christ’ in this context, and to the relevance of what Paul says elsewhere about homosexuality, reveals ‘against his own body’ to be a mere rhetorical flourish and not, as is commonly thought, an assertion of the moral uniqueness of fornication.\n4207 Une plus grande attention a la signification de 'Christ' dans ce contexte, et à ce que Paul dit ailleurs au sujet de l'homosexualité, montre bien que l'expression ‘contre son propre corps’ est une simple fleur de rhétorique – et non pas, comme on le pense souvent, une affirmation sur ce que la fornication a d'exceptionnel du point de vue moral.\n4207 \n4207